Analysis Correlation Diet and Physical Activity with The Incidence of Wet Dreams (Nocturnal ejaculation) in Adolescents at SMPN 1 Kendari - Amiruddin, Amiruddin; Sirih, Muhammad; Munir, Asmawati; Nurhidayah, Dwi; Aldi, Aldi (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Adolescence is the time when a boy begins to enter puberty. Puberty is a sign that a boy begins to mature, one of which is characterized by the occurrence of wet dreams. Many factors influence the occurrence of wet dreams such as diet and physical activity. This study aims to determine the relationship between diet and physical activity with the incidence of wet dreams (Nocturnal ejaculation) in adolescents at SMPN 1 Kendari. The population of this study were male students in grades VII and VIII of SMPN 1 Kendari, totaling 188 people. The sampling technique was Proportional Stratified Random Sampling so that a sample of 128 respondents was obtained. Data collection techniques were carried out by analytic survey through a cross sectional approach. Data analysis techniques using Kendall Tau correlation coefficient test. The results showed that the diet of students in the good category was 9 respondents (7%), 98 respondents (77%) in the moderate category, 21 respondents (16%) in the poor category, and 13 respondents (10%) in the high category, 94 respondents (74%) in the moderate category, 21 respondents (16%) in the low category. The conclusion of this study is that diet and physical activity are related to the incidence of wet dreams (p < 0.05), this is because the better the diet and physical activity of a person, the faster the occurrence of wet dreams.